COLLECTIVE MEMORY IN MOTION: CULTURAL PRACTICES AND THE CONSTRUCTION OF SOCIAL IDENTITIES (Interdisciplinary Studies Journal, 2025)
This article aims to analyze the interrelationship between collective memory and cultural practices in the construction and maintenance of collective identity in different sociocultural contexts. A systematic literature review method was adopted, analyzing national and international scientific publications between 2000 and 2025. The results indicate that cultural practices, such as rituals, celebrations, and oral traditions, are essential symbolic devices for activating and updating collective memory, and are fundamental for the transmission of values, social cohesion, and identity resistance. It is noteworthy that collective memory is not static, but dynamic, continually renewing itself through these practices, especially in contexts of historical oppression and sociopolitical transformations. The articulation between memory and cultural practices is therefore a strategic field for understanding social identities, highlighting the importance of cultural policies that value diversity and strengthen community ties.
Keywords: Cultural transmission; Social cohesion; Identity; Cultural practices; Collective memory